Exploring internal critique: theoretically developed critical commentary on the Self-Appraisal of critical disability studies - Flynn, Susan (My University, 2021)
This article presents theoretically developed critical commentary as an intervention into existing debates about the self-appraisal of Critical Disability Studies (CDS). CDS deploys critique, not just outwardly, toward questions about the nature of dis/ability, able-bodiedness and existing theoretical responses, but also inwardly, toward questions about the veracity of its own conventions. The proposition is that the distinct epistemological and intellectual ambience of CDS provides an environment conducive to productive critical self-appraisal. It is further argued that the culture and form of internal critique in CDS may be better capitalised upon, or productively repurposed back into wider disability studies, to attend to some of the internal tensions and contradictions evident there. In making its case, the paper also explores the speculative boundaries between wider disability studies and CDS.
PUBLISHED
Keywords: Critical disability studies; Critique; Self; Self-reflexivity; Inclusive Society